Introduction: Francophone and Lusophone Literatures in Africa - Claire L. Dehon (Studies in 20th & 21st Century Literature, 1980)
Introduction to the special issue
Keywords: African literature; European languages; francophone literature; lusophone literature; French African literature; Maghreb; North Africa; black African; West and Central Africa; Caid Ben Cherif; Abdelkader Hadj-Hamou; René Maran Ousmane Socé; litterature engagée; négritude movement; Senghor; Césaire